46. THE FINGERPRINT PATTERN OF CD34 IN NEUROFIBROMA. (February 2015) - Ryan, D.; Wright, G.
Abstract : Background: The histological features of desmoplastic melanoma and neurofibroma can be similar in many instances. The unique fingerprint staining pattern of CD34 may aid in making the correct diagnosis. Case: A 64 year old Caucasian male with history of neurofibromatosis had a pigmented skin lesion excised from his medial left clavicle. The histology showed a dermal spindled cell neoplasm with crowding of melanocytes at the dermoepidermal junction. The lesion was positive for S100 and negative for HMB45, Melan-A, keratin and SMA. A CD34 stain was performed and was diffusely positive throughout the lesion. The positive staining was seen between the collagen bundles in a curvilinear configuration with an appearance resembling a fingerprint pattern. Discussion: In normal skin, CD34 reactivity is found in blood endothelial cells, in interstitial and perivascular spindle-shaped and dendritic cells of the reticular dermis, in elongated cells around the midportion of the hair follicles and in spindle cells around the secretory coils of the eccrine sweat glands. There are numerous cutaneous lesions which show positive CD34 staining including but not limited to DFSP, acral superficial fibromyxoma, solitary fibrous tumour, schwannoma and blue nevi. However the CD34 fingerprint staining pattern is believed to be unique to neurofibroma, perineuroma and DFSP. There is uncertainty as to what the positive labelling is within these lesions which creates the fingerprint pattern. It is postulated that it is positive staining of the endoneurial fibroblasts or perineurial-like cells. In contrast to the fingerprint pattern seen in neurofibromas, the CD34 in desmoplastic melanomas is rarely positive and is often patchy when it is. This case demonstrates the challenge in making the distinction between desmoplastic melanoma and neurofibroma due to their similar histological and immunohistochemical profile and the use of CD34 stain as a potential diagnostic tool. Conclusion: In the appropriate clinical context with supporting histology and immunohistochemistry the CD34 stain can be useful in making the distinction between desmoplastic melanoma and neurofibroma.